RELATIONSHIP BETWEEN DIABETES MELLITUS AND PANCREATIC CANCER - A. A. Kashintsev; N. Yu. Kokhanenko (Сибирский онкологический журнал, 2016)
Experience of treating 183 pancreatic cancer patients was summarized. The frequency of carbohydrate metabolism disorder and time dependence between the onset of diabetes and pancreatic cancer detection were examined. It was found that 133 (72.7 %) patients had glucose intolerance. Diabetes mellitus was detected in 49 (26.8 %) patients and 28 of them (57.2 %) had new-onset diabetes. In the latter group of patients, it can be considered that detection of endocrine disease was an early sign of pancreatic cancer.